S73. RELATIONSHIP OF COGNITIVE ABILITY AND PERSONALITY TRAITS WITH HOSTILE ATTRIBUTION BIAS IN NONCLINICAL SUBJECTS: THEORY OF MIND AS A MEDIATOR - Jun Koo, Se; Jin Kim, Ye; Seo, Eunchong; Yoon Park, Hye; Eun Min, Jee; Bang, Minji; Lee, Eun; Kyoon An, Suk (Schizophrenia bulletin, 2020)
BackgroundHostile attribution bias has been reported to be common from nonclinical population to serious mental illness such as schizophrenia and is known to be closely related to social cognition. The aims of this study was to investigate whether theory of mind (ToM) skills mediate the relationship between cognitive ability and personality traits and attribution bias by using the Korean version of Reading the Minds in the eyes test (K-RMET).MethodsOne hundred ninety-six (101 females) nonclinical youths were recruited. To assess general cognitive ability and ToM skills, participants were asked to complete the Raven’s Standard Progressive Matrices (SPM) and the K-RMET. For personality traits, the Eysenck Personality Questionnaire (psychoticism) and Interpersonal Reactivity Index (perspective taking) were administered. To evaluate the hostile attribution bias, the Ambiguous Intentions Hostility Questionnaire was also administered. Path analysis and the bias‐corrected percentile bootstrap method were performed to estimate the parameters of mediating effects.ResultsBased on Akaike Information Criterion(AIC) the best model characterized 1) two direct pathways from psychoticism and the K-RMET to hostility attribution bias and 2) four indirect pathways, wherein SPM, perspective taking and psychoticism influence hostile attribution bias through the K-RMET. The K-RMET fully mediated the association between SPM (p=.028), perspective taking (p=.027), psychoticism (p=.041) and hostile attribution bias.DiscussionThe main findings suggested that ToM skill such as the RMET plays an important role in explaining the relationship between cognitive ability and personality traits and hostile attribution bias. The development of remediation strategy of theory of mind skills may be needed to balance the enhanced hostility bias which is underlying the paranoia.